2021
DOI: 10.7759/cureus.14828
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Vitamin D Deficiency in Patients of Asthma

Abstract: IntroductionAsthma is a clinical syndrome characterized by reversible and recurrent airway obstruction leading to the symptoms of wheezing, cough, shortness of breath, fatigue, and respiratory distress. It is one of the most common lung pathologies worldwide. Its incidence is on the rise in Pakistan, which may be due to overt environmental pollution or improving screening protocols. Irrespective more and more patients are now being diagnosed as cases of asthma and this has led to renewed interest in research f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In many recent studies, vitamin D supplement has been suggested to have positive impact on the reduction of COVID-19 fatality [23] , [24] , [25] . Insufficiency of vitamin D contributes to decrease lung function and accelerate asthma exacerbations [26] . Moreover, it has been demonstrated that vitamin D is involved in a wide spectrum of immunomodulatory activities [27] , [28] .…”
Section: Introductionmentioning
confidence: 99%
“…In many recent studies, vitamin D supplement has been suggested to have positive impact on the reduction of COVID-19 fatality [23] , [24] , [25] . Insufficiency of vitamin D contributes to decrease lung function and accelerate asthma exacerbations [26] . Moreover, it has been demonstrated that vitamin D is involved in a wide spectrum of immunomodulatory activities [27] , [28] .…”
Section: Introductionmentioning
confidence: 99%